Implementasi Pendekatan Berdiferensiasi Bermodel Addie Dengan Media Prezi Dalam Pembelajaran Teks Biografi Di Fase E - Sihombing, Friska Jayanti; Sitorus, Pontas Jamaluddin; Gusar, Martua Reynhat Sitanggang (Jurnal Kajian Ilmu Pendidikan (JKIP), 2025)
This study aims to determine the implementation of the Addie modeled differentiated approach with Prezi media in biographical text learning in phase E. This study uses a quantitative experimental research method with a Two Group Post Test Only Control Design. The population in this study was all 60 students of class X. This study used two classes, namely the control class and the experimental class. The data analysis techniques used were normality test, homogeneity test, and hypothesis test. After conducting research for experiments in the control and experimental classes with the implementation of the Addie modeled differentiated approach with Prezi media, the average value of the control class was 64 with a standard deviation of 42 and the average value of the experimental class was 89 with a standard deviation of 60. The results of the prerequisite test for the control and experimental class data stated that the samples were normally distributed and homogeneous. From the results of the research hypothesis testing, a "t" test was carried out at a significance level of α = 0.05, obtained Thitung> Ttabel = (14.12286> 1.67155). Thus, it was concluded that there was a significant influence on the implementation of the Addie modeled differentiated approach with Prezi media on biographical text learning in phase E.